Training of producing functional fermented food ‘kimchi’ - Putri Widyanti Harlina (Universitas Muhammadiyah Magelang, 2022)
The effort to maintain the immune system in the body is by consuming probiotic foods. Kimchi as a probiotic food can increase the body's immunity. The purpose of this community service program is to improve kimchi making skills and develop community knowledge and skills regarding the importance of nutritional intake of functional fermented foods that can increase immunity in efforts to prevent Covid-19. The service method is carried out with lectures, discussions and training on making kimchi. With this training, participants can increase their understanding of nutritional intake to improve the immune system as a preventive measure against Covid-19. In addition, it can also increase creativity in the independent procurement of functional probiotic food.